Advances in Knowledge Discovery and Data Mining 16th Pacific-Asia Conference, PAKDD 2012, Kuala Lumpur, Malaysia, May 29-June 1, 2012, Proceedings, Part I - Tan, Pang-Ning.; Chawla, Sanjay; Ho, Chin Kuan.; Bailey, James; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The two-volume set LNAI 7301 and 7302 constitutes the refereed proceedings of the 16th Pacific-Asia Conference on Knowledge Discovery and Data Mining, PAKDD 2012, held in Kuala Lumpur, Malaysia, in May 2012. The total of 20 revised full papers and 66 revised short papers were carefully reviewed and selected from 241 submissions. The papers present new ideas, original research results, and practical development experiences from all KDD-related areas. The papers are organized in topical sections on supervised learning: active, ensemble, rare-class and online; unsupervised learning: clustering, probabilistic modeling in the first volume and on pattern mining: networks, graphs, time-series and outlier detection, and data manipulation: pre-processing and dimension reduction in the second volume.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Algorithm Analysis and Problem Complexity; Computer Communication Networks